New South American genus and species of Pteroplatini (Coleoptera, Cerambycidae, Cerambycinae) - Napp, Dilma S.; Martins, Ubirajara R. (Zootaxa, 2006)
A new genus, Acabyara, and a new species, A. aruama, are described from Brazil (Amazonas, Rondonia) and Colombia (Amazonas). A key to the genera of Pteroplatini is provided.